Leadership Failure and Acute Youth Unemployment in Nigeria - Ugo Chuks Okolie; Mevayerore Daniel Igbini (RUDN Journal of Public Administration, 2020)
The history of Nigeria is tainted with the absence of good moral and ethical values in the conduct of the ruling elites; this has adversely affected economic growth and development. Continued poverty reinforced by acute youth unemployment is a barrier to Nigerias quest for consolidating her democracy. A society of beggars, parasites and bandits cannot develop. Youth unemployment has been and is still a major problem in Nigeria. The statistics is staggering despite the political clamours against unemployment. The root of this problem originated in the visionless, selfish, mediocre, tribalistic and opportunistic small money-minded people masquerading as leaders who have continued to regenerate Nigerian political landscape over time. It is against this backdrop that this study examines the relationship between leadership failure and acute youth unemployment in Nigeria. A cross-sectional method was adopted and data was collected via a survey of three hundred (300) respondents in south-south geopolitical zone of Nigeria using non-probability sampling technique. Data collected were analyzed using correlation and linear regression analysis with the aid of Statistical Package for Social Science (SPSS) version 21. The results of the study revealed that there is significant relationship between leadership failure and acute youth unemployment. As predicted, the study also showed that leadership failure exerts a positive and statistically significant impact on acute youth unemployment in Nigeria. On the basis of these findings, the study recommends among others that the government at all levels should empower the jobless youths through genuine empowerment schemes that would equip them to be self-employed and employer of labor, revamped agricultural development schemes to create job opportunities for the unemployed youths roaming about on the Nigeria streets and the actualization of youth empowerment would be impossible if the war against corruption is not intensified.